Aplikasi Konsep Rekreatif pada Perencanaan Desain Budidaya dan Pengolahan Aren di Tuban - Pamungkas, Danny Tri; Laksono, Sigit Hadi; Nareswarananindya, Nareswarananindya (Institut Teknologi Adhi Tama Surabaya, 2021)
Abstract. Palm tree (Arenga pinnata Merr.) is a multipurpose tree and it has been known that palm tree produces industrial materials. In East Java, palm plant spreads in all of north coast, especially in Tuban. Based on the problem, Palm Cultivated and Processing Center is designed to support government's plans and programs in the develop of the first cultivation and processing palm plant in Indonesia with the theme of Agro-tourism. The design concept is